The ocean economy: Trends, impacts and opportunities for a post COVID-19 blue recovery in developing countries - David Vivas Eugui; Diana Barrowclough; Claudia Contreras (South Centre, 2021)
This paper discusses preliminary and still quite unknown trends on trade, finance, and technology of the ocean economy, outlines key impacts and measures taken to respond to the COVID-19 pandemic and raises awareness about the potential of the ocean economy to contribute to a sustainable and resilient recovery. Based on these findings, the paper argues that sustainability and resilience considerations should be more highly prioritized in ocean-based value chains in a post COVID-19 recovery. To support this, the paper highlights the importance of securing sufficient and reliable long-term investment and the creation of capacities to develop new and adapt existing service innovations. It calls for a global trade, investment and innovation Blue Deal as sister to the Green New Deal already gaining support around the world, particularly for developing countries.
Keywords: 300